Stevens Johnson Syndrome—An Adverse Drug Reaction Occurred after Uncomplicated Removal of an Intracerebral Cavernous Hemangioma - Akhavan-Sigari, Reza; Rohde, Veit; Abili, Mehdi (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background Toxic epidermal necrolysis (TEN) is a rare, severe adverse drug reaction. Steven-Johnson syndrome (SJS) represents the milder end of the spectrum. The exact pathogenesis of TEN and SJS is still unknown. Many drugs, including prednisolone, cyclosporin, and intravenous immunoglobulin (IVIG), have been used in an attempt to halt the disease process. The use of phenytoin as a prophylactic anticonvulsant after brain surgery, particularly for brain tumors, is a common practice, regardless of whether the patient has a previous history of convulsions. This treatment policy assumes that the benefits exceed the risks.Case In this paper, we describe a young patient who underwent a total removal of an intracerebral cavernous hemangioma following development of SJS after taking phenytoin postoperatively.Conclusion We suggest that the practice of routine use of phenytoin following brain surgery should be re-evaluated because the treatment may be neither essential nor without side effects.
Keywords: Phenytoin; Steven-Johnson syndrome; adverse drug reaction